MEMPERSIAPKAN ANAK MASUK SEKOLAH DASAR - Evi Deliviana (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Indonesia, 2017)
ABSTRACT This article was made to discuss government regulations regarding the chronological age limit of children to enter elementary school, which is 7 years old. In fact, many parents cannot wait to get their children to enter elementary school even if their children age is not sufficient. This article is prepared based on the literature review to explain the readiness indicators for children to entering elementary school and the importance of a child to have school readiness. The authors use literature study method that is based on: 1) abstract of research result, 2) journal review, and 3) reference book. Based on the results of the study, the authors found that the readiness of children to enter elementary school is not only determined by chronological age alone but also by aspects of cognitive development, language, motor, socioemosional, and independence of children. Another factor that influence the school readiness of children to enter elementary school are environmental support such as family and school. Through a comprehensive understanding of indicators of school readiness of children to enter elementary school, parents are expected to be more sensitive in seeing and taking a raft of whether the child ready to enter elementary school or not. Keywords: school readiness, elementary school ABSTRAK Tulisan ini berawal dari adanya peraturan pemerintah mengenai batas usia kronologis anak untuk masuk Sekolah Dasar, yaitu 7 tahun. Pada kenyataanya, banyak orang tua yang tidak sabar untuk memasukkan anak mereka ke Sekolah Dasar meski dari segi usia belum mencukupi. Tulisan ini disusun berdasarkan pada literatur review yang bertujuan untuk menjelaskan indikator kesiapan anak masuk Sekolah Dasar dan pentingnya seorang anak untuk memiliki kesiapan sekolah. Penulis menggunakan metode studi literatur yang bersumber pada: 1) abstrak hasil penelitian, 2) review jurnal, dan 3) referensi buku. Berdasarkan hasil telaah, penulis mendapati bahwa kesiapan anak masuk Sekolah Dasar bukan hanya ditentukan oleh usia kronologis saja akan tetapi ditentukan juga oleh aspek perkembangan kognitif, bahasa, motorik, sosioemosional, serta kemandirian anak. Faktor lain yang turut mempengaruhi kesiapan sekolah anak adalah dukungan lingkungan seperti keluarga dan sekolah. Melalui pemahaman yang komprehensif mengenai indikator kesiapan anak masuk Sekolah Dasar, diharapkan orangtua semakin peka dalam melihat dan mengambil keputusan apakah anaknya telah siap untuk masuk Sekolah Dasar. Kata Kunci: Kesiapan sekolah, Sekolah Dasar